Child protection law in Libya against online pornography : a comparative perspective - Eldufani, Naeima A. Ahmed (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2018)
The phenomenon of online pornography and its exposure to children has risen in globally. It is indeed an alarming trend with harmful consequences on the moral behaviour of children. The trend has spread to Libya, too. In 2013, almost a million porn websites were blocked by the Libyan Ministry of Communication and Information because they attracted around 30% to 40% of the Internet users in the country. This dissertation evaluates the adequacy of the present laws in Libya on online child protection. It also examines the adequacy of the Draft Law (March 2016) on Cyber Crimes. The researcher studies how these laws prevent child exposure to negative and risky influences of online pornography. The researcher also focuses on the possible improvements to the law by employing critical and comparative analysis with reference to other Arab Laws as well as experiences from international legal initiatives and good practices to combat online child pornography. It is discovered that the Libyan penal laws require some important amendments and improvements to criminalize a number of conducts which threaten children in the cyber world in order to provide effective online child protection in Libya.